Hierarchical silicon nanowires-carbon textiles matrix as a binder-free anode for high-performance advanced lithium-ion batteries - Liu, Bin; Wang, Xianfu; Chen, Haitian; Wang, Zhuoran; Chen, Di; Cheng, Yi-Bing; Zhou, Chongwu; Shen, Guozhen (Scientific reports, 2013)
Toward the increasing demands of portable energy storage and electric vehicle applications, the widely used graphite anodes with significant drawbacks become more and more unsuitable. Herein, we report a novel scaffold of hierarchical silicon nanowires-carbon textiles anodes fabricated via a facile method. Further, complete lithium-ion batteries based on Si and commercial LiCoO 2 materials were assembled to investigate their corresponding across-the-aboard performances, demonstrating their enhanced specific capacity (2950 mAh g −1 at 0.2 C), good repeatability/rate capability (even >900 mAh g −1 at high rate of 5 C), long cycling life and excellent stability in various external conditions (curvature, temperature and humidity). Above results light the way to principally replacing graphite anodes with silicon-based electrodes which was confirmed to have better comprehensive performances.